Duloxetina para melhoria na qualidade de recuperação anestésica em histerectomia abdominal - Castro-Alves, Lucas Jorge Santana de [UNESP] (2016)
Background. Postsurgical quality of recovery is worse in female than that in male patients. Duloxetine has been used successfully for the treatment of chronic pain conditions, but its use for preventing acute postoperative pain has been limited to a single previous study. More importantly, the effect of preoperative duloxetine on global postoperative quality of recovery has yet to be evaluated. The main objective of the current investigation was to evaluate the effect of perioperative duloxetine on postoperative quality of recovery in women undergoing abdominal hysterectomy. Methods. The study was a prospective, randomized, placebo-controlled, double-blinded trial. Female patients undergoing abdominal hysterectomy were randomized to receive duloxetine (60mg orally 2 hours before surgery and 24 hours after surgery) or an identical placebo pill. The primary outcome was the quality of recovery-40 score at 24 hours. Secondary outcomes included opioid consumption and postoperative pain scores. A P value <0.05 was used to reject type I error. Results. Seventy patients were recruited, and 63 completed the study. The median difference (95% confidence interval) in global recovery scores (quality of recovery-40) at 24 hours after surgery between the duloxetine and the placebo group was 9 (4–20) (P < 0.001). Total opioid consumption was reduced at 24 hours in the duloxetine group compared with the placebo group, median (interquartile range) of 1 (0–5) mg IV morphine compared with 5.5 (0.5–9) mg IV morphine (P = 0.004). Nausea, vomiting, and time to postanesthesia care unit discharge were not significantly reduced in the duloxetine group compared with placebo. Conclusions. Duloxetine improves postoperative quality of recovery after abdominal hysterectomy. In addition, duloxetine reduces postoperative opioid consumption, even in the presence of a robust multimodal analgesic strategy. Duloxetine seems to be a viable pharmacologic strategy to improve postoperative quality of recovery in female patients undergoing abdominal hysterectomy.